The Influence of Emotional Intelligence on the Academic Achievement of Grade IX Students at SMP Negeri 1 Maiwa - Kasmiati; Muhammad Hanafi; Rosmini Kasman; Jumiati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to determine whether there is a significant relationship between emotional intelligence and students’ academic achievement. The focus of the research is on ninth-grade students at SMP Negeri 1 Maiwa in the subject of Indonesian Language. The research method used is quantitative with an ex post facto approach and a correlational design. The instrument used was an emotional intelligence questionnaire based on a Likert scale and documentation of academic scores. The analysis results indicate that there is no significant correlation between emotional intelligence and students’ academic performance. With a significance value of 0.796 and a determination coefficient of only 0.1%, it can be concluded that emotional intelligence is not a dominant factor influencing academic achievement in this context. However, clustering analysis suggests that emotional intelligence may contribute to stability in the learning process. Therefore, educational approaches should consider students’ emotional aspects.